2007
DOI: 10.1016/j.jfms.2006.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Cystic liver disease related to high Platynosomum fastosum infection in a domestic cat

Abstract: Platynosomum fastosum is a small fluke found in the biliary ducts and gallbladder of cats. Its lifecycle includes the snail Sublima octona as intermediate host, and lizards, toads and geckos as paratenic hosts. Affected cats are usually adult and acquire the parasite by feeding on infected lizards. This parasite occurs across the world but is more frequent in tropical areas. The clinical signs range from none to obstruction of the biliary tract, with hepatic failure and death, reinforcing the necessity of incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
31
0
5

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 7 publications
2
31
0
5
Order By: Relevance
“…fastosum parasites the bile and pancreatic ducts of cats, having a wide distribution in the Americas and also in Malaysia, Hawaii and West Africa (BOWMAN et al, 2002). In Brazil, Ferreira et al (1999) showed prevalence of 37.2% in Rio de Janeiro, with sporadic cases of occurrence of the parasite associated with liver disorders (XAVIER et al, 2007;VIEIRA et al 2009). Furthermore, it should be remembered by veterinarians as a differential diagnosis in cases of liver diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…fastosum parasites the bile and pancreatic ducts of cats, having a wide distribution in the Americas and also in Malaysia, Hawaii and West Africa (BOWMAN et al, 2002). In Brazil, Ferreira et al (1999) showed prevalence of 37.2% in Rio de Janeiro, with sporadic cases of occurrence of the parasite associated with liver disorders (XAVIER et al, 2007;VIEIRA et al 2009). Furthermore, it should be remembered by veterinarians as a differential diagnosis in cases of liver diseases.…”
Section: Discussionmentioning
confidence: 99%
“…larvae are responsible for a linear, tortuous, erythematous, and intensely pruritic eruption of the human skin called human cutaneous larva migrans . Other organs such as the liver and lungs may also be affected by helminths, and despite not presenting zoonotic potential, they may be a frequent cause of risks to the health of their hosts, especially Platynosomum fastosum, which causes hepatic diseases in cats (FERREIRA et al, 1999;XAVIER et al, 2007), and Aelurostrongylus abstrusus, in cardiopulmonary cases (TRAVERSA et al, 2010). Despite the extensive parasitic fauna described in cats (BOWMAN et al, 2002), studies have shown, by examination of fecal samples or necropsies of cats, that parasitic fauna varies across geographical regions according to season, rural or urban areas, and other factors (CALVETE et al, 1998;LABARTHE et al, 2004;ABU-MADI et al, 2008;GATES;NOLAN, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The most common microscopic lesions include cholangiectasis, cholangiohepatitis, atrophy of hepatocytes, and hyperplasia of the biliary duct epithelium, which results in thickening of the liver, fatty infiltration of hepatocytes, sections of flukes and/or eggs in the liver, and abundant hepatic infiltration of leukocytes and eosinophils (BASU & CHARLES, 2014). However, most cases of platynosomiasis in cats have been described as incidental findings during necropsies (O'SULLIVAN et al, 1976;HANEY et al, 2006;XAVIER et al, 2007;CARREIRA et al, 2008;LENIS et al, 2009;ANDRADE et al, 2012). Therefore, the present study aimed to describe the macroscopic and microscopic liver injuries associated with natural P. fastosum infection in stray cats in an endemic area of midwestern Brazil, and to investigate an association between parasite burden and pathological and biochemical findings.…”
Section: Introductionmentioning
confidence: 99%
“…Although these parasites are spread throughout the world, they are more frequently found in tropical countries. They are small flukes found in the bile ducts and gallbladder of cats and their intermediate hosts include the snail Sublima octona, while lizards and toads could also be paratenic hosts (Xavier et al 2007).…”
Section: Introductionmentioning
confidence: 99%